If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -4x = -7x + 5 Reorder the terms: 11 + -4x = 5 + -7x Solving 11 + -4x = 5 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 11 + -4x + 7x = 5 + -7x + 7x Combine like terms: -4x + 7x = 3x 11 + 3x = 5 + -7x + 7x Combine like terms: -7x + 7x = 0 11 + 3x = 5 + 0 11 + 3x = 5 Add '-11' to each side of the equation. 11 + -11 + 3x = 5 + -11 Combine like terms: 11 + -11 = 0 0 + 3x = 5 + -11 3x = 5 + -11 Combine like terms: 5 + -11 = -6 3x = -6 Divide each side by '3'. x = -2 Simplifying x = -2
| 5/8(X-6)=2+4X | | 5x^2-16x-12=0 | | 47.5=9.5 | | 9.5=47.5 | | 81-9= | | -76=26m | | -24(3)-4= | | 2*x^2-7*x-15=0 | | 5x^2-18x-21=0 | | y+7-6= | | 21-3(4-1)= | | 324(1-x)=36 | | 18.8=2*3.14*r | | -7a^2b+2ab^2= | | 210=4*9*5+2*5*H | | x^2-11x+82=0 | | 2x+3=5x-5/3 | | y+x=r | | 2(x+9)=3(x-3) | | 78=2x-12 | | 9=y+c | | 20+b=a | | 4/3=x+2/8 | | 5w+6=16w-3w+54 | | 9y-14=6y-2 | | -3w+11=-8w+51 | | y=7x^2-4x | | 7x-5y-10=0 | | 24=-11y-8+3y | | 60*0.2= | | 3w-4=-16 | | -32=w/5-7 |